2013
DOI: 10.1177/0956462413506887
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin recovery among HIV-1 infected patients on zidovudine-based antiretroviral therapy and other regimens in north-central Nigeria

Abstract: Objective To assess trends in hemoglobin recovery among HIV-infected patients initiated on zidovudine-based combined antiretroviral therapy (cART) stratified by baseline hemoglobin level. Methods Hemoglobin data from non-pregnant adult patients initiating cART in rural north-central Nigeria between June 2009 and May 2011 was analyzed using a linear mixed effects model to assess the interaction between time, zidovudine-containing regimen, and baseline hemoglobin level on the outcome of subsequent hemoglobin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…23, 24 North-central Nigeria is a region of the country with an adult HIV prevalence of 7.5% compared to the national HIV prevalence of 3.6%. 25 The prevalence of HIV among pregnant women in Niger and Kwara states is estimated to be 4.0% and 2.2%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…23, 24 North-central Nigeria is a region of the country with an adult HIV prevalence of 7.5% compared to the national HIV prevalence of 3.6%. 25 The prevalence of HIV among pregnant women in Niger and Kwara states is estimated to be 4.0% and 2.2%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this patient population, which included patients who were ART-naive and those receiving ART, 85% had anemia, and the prevalence of severe or life-threatening anemia was more than 30%. Previous studies in sub-Saharan Africa have also reported a similarly high prevalence of HIV-related anemia, sometimes approaching as high as 90% [ 3 , 5 , 6 , 32 ]; however, such estimates are largely derived among ART-naive, ambulatory outpatients. The high prevalence of severe or life-threatening anemia observed in this study was in part due to the inclusion of patients ill enough to seek acute medical attention, as well as advanced HIV/AIDS disease, and a high rate of opportunistic infections, notably TB.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the unprecedented scale-up of antiretroviral therapy (ART) in sub-Saharan Africa over the last decade, morbidity and mortality among hospitalized inpatient persons infected with human immunodeficiency virus (HIV) remain very high [ 1 , 2 ]. Anemia is the most common hematological complication of HIV disease, it is highly prevalent among persons living with HIV/acquired immune deficiency syndrome (AIDS) in sub-Saharan Africa [ 3 6 ], and it may be an important driver of morbidity and mortality among inpatients infected with HIV. HIV-related anemia is associated with fatigue, decreased quality of life [ 7 ], and a greatly increased mortality risk [ 8 – 11 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is problematic, as CD4z cell count is a determining factor in ART initiation, 18,19 and haemoglobin testing is important in establishing the presence of anaemia, a common side effect of ZDV-containing regimens (a standard regimen in our population). 20,21 We posit possible explanations for this finding. First, changes in programme leadership in the second year of the programme likely reduced the intensity of logistics coordination for laboratory testing, including CD4z cell count and haemoglobin.…”
Section: Discussionmentioning
confidence: 99%